Changes in the PGC-1α and mtDNA copy number may play a role in the development of pelvic organ prolapse in pre-menopausal patients - Mou-Jong Sun; Yu-Shan Cheng; Chin-San Liu; Ryan Sun (Elsevier, 2019)
Objective: The alternations of mtDNA may play an important role in the molecular pathogenesis and process of Pelvic Organ Prolapse (POP) formation in both pre-menopausal and post-menopausal women. The aim of the present study is to analyze the association between the mitochondrial biogenesis gene and development of POP in the uterosacral ligaments (UL) of pre-menopausal women. Materials and methods: Seventy one pre-menopausal women, all below 52 years of age, were enrolled in this study. UL biopsies were obtained from uterine specimens taken from 33 women with POP (n = 33, study group) and 38 myoma patients without POP (n = 38, control group). Quantitative Real-Time PCR was performed to measure mitochondrial DNA (mtDNA) copy number and mtDNA4977. Western blotting and immunohistochemistry were used to assess the protein expression of PGC-1α, TFAM, NRF-1 and NRF-2. Statistical analysis was performed using SPSS statistical software and the Mann-Whitney U test, and the continuous variables were analyzed using the Student's t-test in demographic data. Results: There were no significant differences in the patient demographics between the two groups (p > 0.05). The mtDNA copy number in the UL of pre-menopausal patients with prolapse was significantly higher than that in the no prolapse group (p = 0.008). There were no significant differences between the mtDNA4977 of the POP and non-POP groups, but a significantly higher expression of PGC-1α in the POP group compared to the non-POP group (1.59 ± 1.30 v.s. 0.66 ± 0.53; p = 0.036). The expression of TFAM in the POP group was higher than in the non-POP group). There was no significant difference in the TFAM(p = 0.377), NRF-1 and NRF-2 expression between the POP and non-POP groups (p = 0.647; p = 0.682). Conclusions: Changes in the PGC-1α and mtDNA copy number may play a role in the development of Pelvic Organ Prolapse in pre-menopausal patients. Keywords: Pre-menopause, Pelvic organ prolapse(POP), Gene expression, Mitochondrial DNA (mtDNA), Molecular pathogenesis